Learning from the past: Vulnerability analysis and cascading hazard classification of the three major volcanic eruptions in Indonesia - Malawani, Mukhamad Ngainul; Hadmoko, Danang Sri; Rachmadan, Firdaus Alif; Pratiwi, Dinda; Hermawan, Hannan Revi; Hayat, Dimas Maula; Laksono, Agung; Wibisono, Hafidz; Handayani, Tiara (Indonesian Journal of Geography, 2025)
This research addresses a significant gap in understanding the social impacts of three major volcanic eruptions in Indonesia: Samalas in 1257, Tambora in 1815, and Krakatau in 1883. While these events have been widely studied in geological and volcanic contexts, their societal impacts and the associated cascading hazards have not been thoroughly compared. Utilizing historical documents that reflect societal memories, including Babad Lombok, Babad Sembalun, Babad Suwung, Syair Kerajaan Bima, and Syair Lampung Karam alongside records from the Dutch East Indies period, this study investigates the community responses and impacts of these catastrophic events. The findings reveal that all documented social memories articulate the communities' reactions and the resultant consequences of these eruptions. Additionally, geological and volcanological data from prior studies were employed to describe the characteristics of past vulnerabilities. Notably, Samalas exhibited the longest recovery process, whereas Krakatau resulted in the highest number of casualties due to its cascading hazards. All events are categorized within the M4 scale of cascading hazards, emphasizing the complexity of these disasters. This research offers critical insights into Disaster Risk Reduction (DRR) programs, highlighting the necessity of integrating historical social memory into modern risk management strategies. By understanding past community responses, DRR initiatives can better prepare for future volcanic events, ensuring a more resilient society. Received: 2024-12-03 Revised: 2025-04-30 Accepted: 2025-08-06 Published: 2025-08-20